I am not against Inclusive Education but…: Teachers’ Voices from Pakistan - Rashida Qureshi, Fatima Razzaq, (JIE, 2024)
Teachers as ‘agents of change’ have an important part in the progressive and meaningful inclusion of children with disabilities in general schools; their positive attitudes toward IE are a pre-requisite for its success. At the same time, teachers' beliefs and predispositions about IE are intertwined with their 'capabilities to make a difference' or in other words teacher agency. The present study has explored these two concepts as Enigmas of IE and Propositions of Agency respectively. The data were collected through a series of focus group discussions with a sample of 70 teachers from general schools of Islamabad Pakistan. Our study points to the co-existence of positive as well as negative attitudes of teachers toward IE. The findings indicate that teachers of general schools may use their agency to resist inclusion in their schools unless and until support structures are put in place. The findings also caution us to explore further whether it is really the anti-IE attitude or under the façade are issues related to the competence and autonomy of teachers rather than their beliefs and predispositions per se.